Raman spectroscopy and ab initio quantum chemical calculations of ion association behavior in calcium nitrate solution. (21st February 2018) - Zhu, Fayan; Zhou, Hongxia; Wang, Xiufang; Zhou, Yongquan; Liu, Hongyan; Fang, Chunhui; Fang, Yan
Abstract: In this work, microscopic Raman spectroscopy and component analysis were used to study a calcium nitrate solution with molar water‐to‐salt ratio (WSR) values of 4–320. The results showed that the symmetrical stretching vibration wavenumber of the nitrate ion ( v 1 ‐NO3 − ) in the solution blue shifted from 1, 048 to 1, 053 cm −1, and the full width at half maximum increased from 9.7 to 11 cm −1 when the WSR was reduced from 320 to 4. The component analysis of v 1 ‐NO3 − showed that the first concentration region was for WSR ≥ 16.3. In this region, solvent‐shared ion pairs (SIPs) were the main species, and contact ion pairs (CIPs) and free‐hydrated ions were the secondary species. For 8.4 ≤ WSR < 16.3, the main species were CIPs; the amount of complex structures in this region increased rapidly, whereas the amount of SIPs decreased rapidly. For WSR < 8.4, the main species were the complex structures, and the amount of CIPs and SIPs dropped rapidly. Ab initio quantum chemical calculations showed that the SIPs in the first concentration range were composed of 2 hexahydrate calcium ions and 1 nitrate ion that formed a shared ion pair, SIP‐SIP. The calcium ions were directly bonded with water molecules, and the nitrate ions formed hydrogen bonds with the water molecules. In the second concentration region, the CIPs were each formed by 2 hydrated calcium ions and 1 nitrate ion via monodentate or bidentate coordination with a CIP‐CIP structure. When the WSR was further reduced, a large number of the complex structures such as Comp5 and Comp6 formed in the solution, which were the complex structures [(H2 O) n Ca 2+ (NO3 − )Ca 2+ (H2 O) m ] clustered by C5 or C6. Abstract : The main species were solvent‐shared ion pairs or free‐hydrated ions when WSR ≥ 16.3. The main species were contact ion pairs when 8.4 ≤ WSR < 16.3. The main species were the complex structures when WSR < 8.4, and the amount of CIPs and SIPs dropped rapidly.